Entrepreneurship and its impact on Indian economy - Singh, Sunita; Shubhalakshmi (2009)
Industrial and commercial development of a society depends much on the enterprising spirit and urge of its people. In India too, many an entrepreneur before and after Independence heralded the industrial and economic activities at various levels. entrepreneurship does not call for establishing only large or medium level industries. In the small scale sector also entrepreneurs have shown grit and achieved success for their ventures on the dint of their enterprising instinct. The article gives an overview of the intrinsic relationship between entrepreneurship and business success in the small scale sector. - Reproduced.
Keywords: Entrepreneurs